Application of experimental statistical method in optimizing preparation variables for Cu-Ni/TiO2 photocatalyst - Bashiri, R. (Trans Tech Publications Ltd, 2014)
Cu-Ni/TiO2 was prepared using solâhydrothermal method. Response surface Method (RSM) including central composite design (CCD) was applied to study the single and combined effects of three primary preparation parameters like water to alkoxide molar ratio (A), acid to alkoxide molar ratio (B), and Cu content (C) on the growth of Cu-Ni doped TiO2 particle size. The particle size range of the photocatalysts was 13â25 nm. Analysis of variance (ANOVA) revealed a secondâorder polynomial regression model to fit the experimental data in CCD. A comparison between predicted and experimental values has depicted a good agreement amongst them with high coefficient of determination value (R2= 0.98). The 3-D response surface and the contour plots imply a synergistic effect of parameter A, an antagonistic effect of parameter B, and significant interaction between them on the growth of particle sizes more than parameter C and its interactions with other variables. The smaller average sizes of Cu-Ni doped TiO2 particles with higher surface area are helpful to increase the light adsorptive property in hydrogen production studies. Â© 2014 Trans Tech Publications, Switzerland.